Atmospheric and light-induced effects in nanostructured silicon deposited by capacitively and inductively-coupled plasma - Saleh, Zaki Mohammad; Nogay, Gizem; Ozkol, Engin; Turan, Rasit (International Journal of Intelligent Systems and Applications in Engineering, 2015)
Renewable sources of energy have demonstrated the potential to replace much of the conventional sources but the cost continues to pose a challenge. Efforts to reduce cost involve highly efficient and less expensive materials as well as enhanced light management. Nanostructured materials consisting of silicon quantum dots in a matrix of amorphous silicon (a-Si) are promising for higher efficiency and better stability. Quantum confinement offers a tunable band gap, relaxes momentum conservation rule, and may permit multi exciton generation, MEG. We employ electron spin resonance (ESR), the temperature dependence of dark and photoconductivity to compare the stability of amorphous and nanostructured silicon films deposited by inductively- and capacitively-coupled plasma against atmospheric and light exposure. Distinctly different behaviors are observed for amorphous and nanostructured films suggesting that nanostructured films are more permeable to oxygen infusion but more resistant to light induced effect